Unstable intertrochanteric femoral fracture care in older population - Mohanty, Rashmiranjan; Jena, Arpita; Mohanty, Ranjan Kumar (International Journal of Research in Medical Sciences, 2024)
Background: The present study aimed to compare outcomes between geriatric patients treated with cementless bipolar hip arthroplasty (BHA) and proximal femoral nail (PFN) for intertrochanteric femur fractures, focusing on postoperative complications, reoperation rates, implant-related issues, and functional outcomes. Methods: The present study took place at PRM medical college, Baripada for a period of 4 years and employed a prospective design with 76 individuals with femoral shaft fractures who underwent surgical treatment, wherein 40 were treated using cementless BHA and 36 with PFN. Evaluation included the HHS at the last follow-up, alongside recorded blood transfusion rates and surgery duration, statistically compared between the two groups. Results: The study involved elderly patients with intertrochanteric femur fractures (average age: 82.9 years). BHA and PFN groups had differing average ages (81.4 and 83.9 years, respectively). Follow-up durations were 18.6 months overall, 23.8 months for BHA, and 13.1 months for PFN. PFN showed advantages in surgery duration and blood transfusion rates. Adverse effects in BHA included 4 epidermal infections, while PFN had 2 epidermal infections and 2 instances of implant malfunction, resulting in extraction. PFN demonstrated a 5.5% cut-out rate. Conclusions: The study compares the outcomes of elderly patients with femoral shaft fractures treated with cementless BHA and PFN. The results indicate that PFN presents advantages over BHA in terms of shorter surgery duration and reduced blood transfusion rates. However, further research and extended review are warranted to draw definitive results about the superiority of either approach.